Oral Communication Ability In English: An Essential Skill For Engineering Graduates - Idrus, Hairuzila; Salleh, Rohani; Lim Abdullah, Muhammad Ridhuan Tony (Penerbit Universiti Sains Malaysia, 2011)
Good communication skills are essential to a person's job performance. Employers are now emphasizing that success as an engineer requires more than simply strong technical capabilities; communication is among the skills that are also needed. In this era of globalisation, English has become one of the most important languages of communication. Thus, it is very important that future engineers be able to communicate well in English. Self-effcacy refers to an individual's belief that he or she is capable of performing a task (Robbins & Judge, 2007). A strong sense of self-effcacy enhances one's accomplishments and personal well-being in many ways (Bandura, 1986). Since communication is an important skill sought after by employers, it is vital to know the self-effcacy of future engineering graduates in order to ensure that they will step into the real world adequately prepared. This article discusses the perceived self-effcacy of 169 senior-year engineering students regarding their ability to communicate in English. A set of questionnaires designed to assess students' levels of self-effcacy was administered. Factor analysis results reveal three underlying constructs for self-effcacy: aptitude, attitude and aspirations. Overall the fndings show that senior engineering students possess high self-effcacy beliefs in all three constructs studied. The implications of the fndings to theory and practice are discussed.